Analisis Kompetensi Pedagogik Guru dalam Perencanaan Bahan Pembelajaran Kelas 6 SDN Kutajaya 2 - Yeni Nuraeni; Sabila Putri Andriani; Della Tirwahyuni; Nia Amalia; Virli Ibtisam Naura A; Intan Safitri (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine the pedagogic competence of classroom teachers in planning learning materials for grade 6 students of SDN Kutajaya 2. In accordance with the Regulation of the Minister of Education and Culture number 62 of 2013 concerning Educational Standards, teachers and schools have an important role in planning or preparing learning materials to be used in learning as a medium so that the material taught is conveyed properly. This research is a descriptive qualitative research that uses observation, interviews, and documentation as data collection techniques. This research involved the Principal, 3 sixth-grade homeroom teachers, and subject one teachers. The results of the study showed that sixth grade teachers were ready to create learning materials. Teachers' skills and creativity, collaboration between teachers, students and parents, learning elements, and adequate facilities and infrastructure are supporting components that affect planning subject matter.